2004
DOI: 10.1007/s00467-004-1709-4
|View full text |Cite
|
Sign up to set email alerts
|

Urine collection pads: are samples reliable for urine biochemistry and microscopy?

Abstract: The aim of the study was to validate the reliability of samples obtained with urine collection pads (UCP) for selected laboratory biochemical analyses, urine cell microscopy, and bedside semi-quantitative stick urinalysis. A series of laboratory experiments was performed to test agreement between urine concentrations, or results, before and after passage through a UCP (incubated for 37 degrees C for 15 min). The following urinalyses were performed: electrolytes, calcium, phosphate, urate, osmolality, pH, prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…This would not be a problem for fresh urine collected directly from an infant as no significant precipitation occurs within the first few hours after collection [5]. All catecholamines showed good agreement between pad and non-pad urine, including samples with very high catecholamine excretion, confirming that use of the pads will give reliable results in children with suspected neuroblastoma or phaeochromocytoma, consistent with previous observations [4]. The pads have not hitherto been evaluated for metabolic tests in children being investigated for inborn errors of metabolism.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This would not be a problem for fresh urine collected directly from an infant as no significant precipitation occurs within the first few hours after collection [5]. All catecholamines showed good agreement between pad and non-pad urine, including samples with very high catecholamine excretion, confirming that use of the pads will give reliable results in children with suspected neuroblastoma or phaeochromocytoma, consistent with previous observations [4]. The pads have not hitherto been evaluated for metabolic tests in children being investigated for inborn errors of metabolism.…”
Section: Discussionsupporting
confidence: 87%
“…A previous study using the same collection pads demonstrated that routine biochemistry results were similar in pad and non-pad urine obtained from adult volunteers [4]. However, urine obtained from infants and young children has a different composition from adult urine, particularly in relation to lower concentrations of sodium and creatinine.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…While a previous investigation noted comparable total protein values in extracted and spontaneously voided urine, [7] a subsequent study demonstrated a 10% reduction in total protein values in extracted samples. [9] Selective adsorption of specific urine proteins (creatinine, albumin, retinol binding protein) by cotton ball fibers has also been described. [10,11] However, the impact of diaper extraction on the urinary proteomic profile has not been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…In men a urethral sheath can be used in patients who cannot produce a specimen whilst, in women, an in-and-out catheter may be the best option 22 . Newcastle urine collection pads (UCPs) represent a non-invasive way of collecting urine, however specimens collected from these are much more useful for dipstick urinalysis than microbiological analysis 35,36 .…”
Section: Obtaining Samplesmentioning
confidence: 99%